Congenital Heart Disesase: A Retrospective Analysis from a Tertiary Referral Centre in Portugal - Faim,Diogo (2021)
Abstract Background: Congenital heart disease is the leading cause of mortality among all congenital malformations. Objectives: To evaluate the incidence of congenital heart diseases in a central maternity hospital in Portugal from January 2003 to December 2018 and to determine survival in the first year of life. Methods: Retrospective analysis of newborns diagnosed with congenital heart diseases within 72 hours after birth. Malformations were divided according to pathophysiology. Cumulative survival analysis was performed by the Kaplan-Meier test. Stastical significance was set at p <0.05. Results: A total of 297 newborns with cardiac malformation was recorded among 47,198 live births (incidence of 6:1000), 16% associated with extra-cardiac disease. The most frequent congenital heart diseases were left-to-right shunt lesions (n = 216), followed by cyanotic (n = 41), acyanotic obstructive (n = 31) and miscellaneous (n = 9). Seventy (24%) patients had prenatal diagnosis, 88% of them cyanotic defects, and a positive association was found between prenatal diagnosis and mortality (p <0.001). Coarctation of the aorta was associated with gestational diabetes (p = 0.014). Atrial septal defect was more common in females (p = 0.02). Mortality rate due to heart disease was 3.4%. Patients with cyanotic disease, 99%, 97%, 97%, respectively, for patients with left-to-right shunt lesions, and 97%, 97%,97% for those with obstructive lesion cases. Conclusion: The incidence of congenital heart disease was 6:1000, mostly left-to-right shunt lesions. Heart disease accounted for only half of deaths, and cyanotic diseases have a high nonspecific mortality rate.